Production based on innovation - Chi, Hoang Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
On the basis of emphasizing the general value of "creativity", it is possible to classify production development into production innovation, science and technology (S&T) innovation and innovation. This is a new approach that allows to understand the production, S&T and innovation, and especially contribute to addressing practical issues such as the differences between countries in terms of innovation, innovative entrepreneurship, venture capital, the role of enterprises in the national innovation system, etc.